2019
DOI: 10.1631/jzus.b1900270
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of an intergeneric conjugation system and analysis of promoter activity in Streptomyces rimosus M527

Abstract: An efficient genetic transformation system and suitable promoters are essential prerequisites for gene expression studies and genetic engineering in streptomycetes. In this study, firstly, a genetic transformation system based on intergeneric conjugation was developed in Streptomyces rimosus M527, a bacterial strain which exhibits strong antagonistic activity against a broad range of plant-pathogenic fungi. Some experimental parameters involved in this procedure were optimized, including the conjugative media,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that an appropriate concentration of Mg 2+ in the medium, or a suitable heat-shock treatment of the cells, or an optimal ratio of donor-to-recipient could give improved frequency of conjugation ( Song et al, 2019 ; Zhang et al, 2019 ). We thus individually assessed each of such factors to attain successful conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that an appropriate concentration of Mg 2+ in the medium, or a suitable heat-shock treatment of the cells, or an optimal ratio of donor-to-recipient could give improved frequency of conjugation ( Song et al, 2019 ; Zhang et al, 2019 ). We thus individually assessed each of such factors to attain successful conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, significant focus has been placed on developing genetic transformation methods and expression systems [16] or ribosome engineering technology combined with new fermentation conditions to improve rimocidin production [17]. The long-term goal of our research is to better understand regulatory mechanisms involved in rimocidin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The gene nsdA sr was placed under the control of promoter ermE * in plasmid pIB139 to create pIB139-nsdA sr (Additional file 3: Figure S3). The plasmid pIB139-nsdA sr was then introduced into S. rimosus M527 by intergeneric conjugation [16], to generate the recombinant strain S. rimosus M527-NA sr resistant to 300 µg/mL apramycin (Additional file 4: Figure S4). The integration of plasmid pIB139-nsdA sr into the chromosome of S. rimosus M527 was verified by PCR (Additional file 5: Figure S5).…”
Section: Construction Of Recombinant Strain S Rimosus M527-na Srmentioning
confidence: 99%
See 1 more Smart Citation
“…
Streptomyces are famous for their ability to synthesize a large number of bioactive compounds as secondary metabolites containing antibiotics, enzyme inhibitors, and other small molecules with potential physiological activity (Niu et al, 2016;Song et al, 2019;Yin et al, 2019). Secondary metabolites are produced by a multi-step reaction of a primary metabolite as a precursor (Liu et al, 2013;Li et al, 2021).
…”
mentioning
confidence: 99%